THE CONTRIBUTION OF WORK MOTIVATION AND DISCIPLINE TOWARDS WORKFORCE PERFORMANCE AT PT. SARIMELATI KENCANA Tbk. - Ela Hardiantini; Angga Juanda; Nuru Kalumidya Erponis (Yayasan Education and Social Center, 2026)
This study aims to determine the contribution of motivation and work discipline to employee performance at PT. Sarimelati Kencana Tbk. This study uses a quantitative method with an associative descriptive approach. The study population was 355 employees, while the study sample was 75 respondents determined using the Slovin formula. Data collection techniques were carried out through questionnaires, while data analysis techniques used validity tests, reliability tests, classical assumption tests, simple linear regression, multiple linear regression, correlation coefficients, determination coefficients, partial t tests, and simultaneous F tests. The results showed that motivation had a positive and significant effect on employee performance, indicated by the regression equation Y = 15.095 + 0.672X1, a correlation value of 0.776, a determination coefficient of 60.3%, and a calculated t value of 10.522 greater than the t table of 1.993 with a significance of 0.000. Work discipline has a positive and significant effect on employee performance, shown through the regression equation Y = 6.438 + 0.825X2, a correlation value of 0.901, a coefficient of determination of 81.2%, and a calculated t value of 17.780 greater than the t table of 1.993 with a significance of 0.000. Simultaneously, motivation and work discipline have a positive and significant effect on employee performance, shown through the regression equation Y = 5.708 + 0.203X1 + 0.664X2, a correlation value of 0.915, a coefficient of determination of 83.7%, and a calculated F value of 184.756 greater than the F table of 3.12 with a significance of 0.000. These findings indicate that improving employee performance can be done through strengthening motivational factors and implementing work discipline consistently.